Fallen Pillars: The Past, Present, and Future Population Dynamics of a Rare, Specialist Coral–Algal Symbiosis - Chan, Andrea N.; Lewis, Cynthia L.; Neely, Karen L.; Baums, Iliana B. (Frontiers in Marine Science, 2019)
With ongoing changes in climate, rare and ecologically specialized species are at increased risk of extinction. In sessile foundation fauna that reproduce asexually via fragmentation of existing colonies, the number of colonies does not reflect the number of genets and thus can obscure genotypic diversity. Colonies that are the product of fragmentation are not visually distinguishable from colonies that stem from sexual recruits. For this reason, molecular markers are necessary to assess genotypic variation and population structure in clonal organisms such as reef-building corals and their endosymbiotic dinoflagellates. For the rare Caribbean pillar coral, Dendrogyra cylindrus, and its endosymbiotic dinoflagellate, Breviolum dendrogyrum, we use de novo microsatellite markers to infer past demographic changes, describe modern population structure, and quantify the frequency of asexual reproduction. Our analyses show that D. cylindrus comprises three distinct populations across the Greater Caribbean whereas the symbiont could be differentiated into four populations, indicating barriers to gene flow differ between host and symbiont. In Florida, host and symbiont populations reproduced mainly asexually, yielding lower genotypic diversity than predicted from census size. When multiple coral ramets were present, they often associated with the same clonal strain of B. dendrogyrum, pointing to the high fidelity of this relationship. Models of past demographic events revealed no evidence for historical changes in population sizes, consistent with the paleontological record of D. cylindrus indicating it has been rare for hundreds of thousands of years. The most recent global thermal stress event likely triggered a severe disease outbreak among D. cylindrus in Florida, resulting in a severe population decline. Projections indicate a high likelihood that this species will become extinct in the Northern Greater Caribbean within a few decades. The ecosystem consequences of losing rare coral species and their symbionts with increasingly frequent extreme warming events are not known but require urgent study.